Vitamin D3 supplementation on lung functions and exercise tolerance in D3 deficient asthma COPD overlap syndrome patients - A randomized controlled trial - Sultana, Naznin; Ali, Taskina; Bennoor, Kazi Saifuddin; Hossain, Md Ali; Mahmud, Maksuda Bintey; Hassan, Samia; Nahar, Salsa Bil; Rosy, Sharkia Khanam; Anjum, Salma (Journal of Bangladesh Society of Physiologist, 2022)
Background: Vitamin D3 supplementation showed significant improvement in lung functions and exercise tolerance in both of asthma and COPD patients. Objectives: To evaluate the effects of vitamin D3 supplementation on lung functions and exercise tolerance in D3 deficient, stable patients with ACO. Methods: A double blinded randomized placebo controlled trial was carried out on 60 (sixty) D3 deficient [serum 25-hydroxycholecalciferol, 25(OH)D<30 ng/ml], male, smoker, stable ACO patients of age 40 to 80 year, selected according to selection criteria. After the final selection, all the patients were randomly allocated as ‘Study’ (n=30) or ‘Control’ (n=30) and their baseline spirometric lung functions (FVC, FEV1, FEV1/FVC ratio, PEFR, FEF25-75) and exercise tolerance represented by 6Minute Walk Distance (6MWD), peripheral capillary oxygen saturation (SpO2) at rest, SpO2 after 6MWT, dyspnea scale and fatigue scale variables were measured. All the ‘Study’ patients received 80,000 IU (2 oral capsules) of vitamin D3 per week for first 13 weeks. Subsequently, according to their serum 25(OH)D or calcium, they got 40,000 IU (1 oral capsule) of D3 per 1 week or per 2 weeks or per 6 weeks or no further supplementation, for following 13 weeks. Whereas, all the ‘Control’ patients received two oral capsules of placebo weekly for consecutive 26 weeks. After 26 weeks of follow up, spirometric lung functions and exercise tolerance variables were again measured and compared with their corresponding baseline value. Data were analyzed by independent and paired sample t test, where p£0.05 was accepted as significant. Results: There was significant improvement in 6MWD (p<0.05), SpO2 after 6MWT (p<0.001), dyspnea scale (p<0.001) and fatigue scale (p<0.001), in patients with vitamin D3 supplementation in comparison to those of placebo on 26th week of follow up. However, there was no improvement in ventilatory variables in the D3 supplemented group in comparison to those of placebo group. Conclusion: The present study reveals that vitamin D3 supplementation improves exercise tolerance but not ventilatory variables in vitamin D3 deficient stable ACO patients. Further multi centered trials with different dose as well as duration schedule on both male and female ACO patients are recommended. J Bangladesh Soc Physiol. 2022, June; 17(1): 21-33